The influence of Lactobacillus rhamnosus LC705 together with Propionibacterium freudenreichii ssp. shermanii JS on potentially carcinogenic bacterial activity in human colon - Hatakka, Katja; Holma, Reetta; El-Nezami, Hani; Suomalainen, Tarja; Kuisma, Minna; Saxelin, Maija; Poussa, Tuija; Mykkänen, Hannu; Korpela, Riitta (International journal of food microbiology, 2008)
The bacterial enzymes β-glucosidase, β-glucuronidase, and urease may contribute to the development of colon cancer by generating carcinogens. A reduction in the activity of these enzymes by certain lactic acid bacteria is considered to be beneficial. This study examined fecal β-glucosidase, β-glucuronidase, and urease activities during administration of Lactobacillus rhamnosus LC705 (LC705) together with Propionibacterium freudenreichii ssp shermanii JS (PJS). Thirty-eight healthy men participated in this randomized, double-blind, placebo-controlled, two-period crossover study with treatment periods of 4 weeks. Subjects consumed daily bacterial or placebo capsules. Bacterial capsules contained viable LC705 and PJS (2 × 10 10 CFU of each strain daily). The activities of β-glucosidase, β-glucuronidase and urease, recovery of LC705 and PJS, and counts of total lactobacilli and propionibacteria were determined from feces. The mean fecal counts of total lactobacilli and propionibacteria as well as strains LC705 and PJS were significantly increased during the administration of bacteria (3.5-, 13-, 80- and 11-fold, respectively). β-glucosidase activity decreased by 10% ( P = 0.18) and urease activity by 13% ( P = 0.16) during bacterial supplementation versus placebo. The change in β-glucosidase activity was negatively correlated with the change in propionibacteria counts ( R = − 0.350, P = 0.039), being − 2.68 versus 0.94 nmol/min/mg protein in subjects with increased and unchanged/decreased propionibacteria, respectively ( P = 0.003). To conclude, the administration of LC705 and PJS was followed by an increase in the fecal counts of lactobacilli and propionibacteria and a decrease in the activity of β-glucosidase with increasing counts of propionibacteria.